Experimental methods to enhance problem - solving skills in early childhood - Nafiqoh, Heni (Indonesian Research Journal in Education |IRJE|, 2025)
This study seeks to improve young children's problem-solving abilities with experimental learning methods that emphasize hands-on involvement in the learning process. Using a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, the study was carried out over two cycles and involved 10 children in Group A (aged 4–5 years), consisting of six boys and four girls. Data was gathered through direct observation of the children's activities and analyzed using descriptive statistics, presented as average percentages. The findings showed a significant increase in problem-solving abilities, from 0% in the initial observation to 30% in the first and 70% in the second cycles. These results suggest that experimental methods can foster independent exploration, observation, and reasoning among young children. The study concludes that learning approaches grounded in experience and exploration are more suitable for developing problem-solving skills in early childhood settings.